Reflections on the Old Swimmin' Hole by Tony Schinkinger - (Author); (Interviewer); (Publisher) (2010)
Notes - Tony Schinkinger recalls his memories of the places he used to swim when he was a child growing up around Athabasca. He recalls going out to the Tawatinaw Creek (which was actually Tawatinaw River), about three miles south of Athabasca on Highway 2 (which was called the Colinton Highway then). The kids would walk out there to swim because it was close to town, and quite shallow to swim in. He recalls how they had been too scared to swim in the Athabasca River for fear that they would be caught in an undercurrent or whirlpool and drown. When the kids got a little older they would swim at a place a little further down the Tawatinaw Creek, known as The Pier because of the "Pier" that CNR had built there to prevent the tracks from being washed away. This swimming hole was larger and deeper than Sandy Beach. Schinkinger recalls being thrown in the water by bigger kids, and therefore learning how to swim. He also remembers roasting potatoes or hot dogs on the river bank and being caught swimming in the nude by a group of girls. He claimed that in those days boys and girls did not play together, so this was a big deal! Neither swimming hole is around anymore, but there is a chlorinated pool in Athabasca for the kids to use (2 pages)